Manifestations of humanism in Cuban history, politics, and culture - Kronenberg, Clive (Department of English Language and Literature, 2014)
The thesis explores what it deems are some of the most perceptible humanistic features in Cuban history, politics, and culture, less specified, or highlighted, or generally not presented in a cohesive body of knowledge in the western scholarly world. In the context of its subject, the thesis embraces rational-critical thinking and supports the custom of non-violent dispute. Insofar as the Cuban Constitution incorporates a range of goals structured on socialist principles, the thesis sets out to scrutinise manifestations in Cuban thinking emblematic of the Marxist-humanist and/or anti-Stalinist philosophical traditions of revolutionary praxis. The thesis' main body investigates, illustrates, and analyses the presence of such features, focussing predominantly on the period 1959 to the late 1960s. Where the thesis does delve into timeframes beyond this era, it endeavours to show the continuity of relevant facets previously identified. Preceding the main examination, the thesis looks into what is widely perceived as the main roots of the country's humanist tradition, the moral ideas and standpoints of Jose Marti, the country's national hero. A further objective of this thesis lies in the belief that aspects of Cuba's national cultural policy in large measure addresses historical issues post-Apartheid South Africa confronts today.